KEPASTIAN HUKUM DAN PERLINDUNGAN HUKUM HAK ATAS TANAH - Hadisiswati, Indri (Ahkam: Jurnal Hukum Islam, 2014)
Giving ownership of land is intended to guarantee rights of people legally. As an implementation of UUPA, the government registers the ownership of land in Indonesia as stated in chapter 19 UUPA. Technically, the basis for registering land is stated in Peraturan Pemerintah Number 10/1961 about land register which is renewed in Peraturan Pemerintah No 24/1997. Kata kunci: Kepastian Hukum, Perlindungan Hukum, Hak atas Tanah